2019
DOI: 10.1038/s41467-019-09628-6
|View full text |Cite
|
Sign up to set email alerts
|

Canonical PRC1 controls sequence-independent propagation of Polycomb-mediated gene silencing

Abstract: Polycomb group (PcG) proteins play critical roles in the epigenetic inheritance of cell fate. The Polycomb Repressive Complexes PRC1 and PRC2 catalyse distinct chromatin modifications to enforce gene silencing, but how transcriptional repression is propagated through mitotic cell divisions remains a key unresolved question. Using reversible tethering of PcG proteins to ectopic sites in mouse embryonic stem cells, here we show that PRC1 can trigger transcriptional repression and Polycomb-dependent chromatin mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 44 publications
5
76
0
Order By: Relevance
“…We individually tested the domain from the RYBP protein as annotated by Pfam (which is just 32 amino acids, thus shorter than the version we had synthesized in our 80 AA domain library) and confirmed rapid silencing of the reporter gene ( Figure 1E). RYBP-mediated silencing was also demonstrated in a recent report of full-length RYBP protein recruitment in mouse embryonic stem cells (Moussa et al, 2019;Zhao et al, 2020). Our result establishes that the 32 AA RYBP domain, which has been shown by surface plasmon resonance to be the minimal required domain to bind the polycomb histone modifier enzyme RING1B (Wang et al, 2010), is sufficient to mediate silencing in cells.…”
Section: Ht-recruit Identifies Hundreds Of Repressor Domains In Humansupporting
confidence: 86%
“…We individually tested the domain from the RYBP protein as annotated by Pfam (which is just 32 amino acids, thus shorter than the version we had synthesized in our 80 AA domain library) and confirmed rapid silencing of the reporter gene ( Figure 1E). RYBP-mediated silencing was also demonstrated in a recent report of full-length RYBP protein recruitment in mouse embryonic stem cells (Moussa et al, 2019;Zhao et al, 2020). Our result establishes that the 32 AA RYBP domain, which has been shown by surface plasmon resonance to be the minimal required domain to bind the polycomb histone modifier enzyme RING1B (Wang et al, 2010), is sufficient to mediate silencing in cells.…”
Section: Ht-recruit Identifies Hundreds Of Repressor Domains In Humansupporting
confidence: 86%
“…We recently demonstrated that removal of cPRC1 complexes in ESCs has little effect on gene repression (Fursova et al, 2019), while earlier work showed that PRC2 removal resulted in few gene expression defects (Riising et al, 2014). This suggests that the mechanisms by which PRC1 catalysis represses transcription do not rely solely on PRC2 and cPRC1 in ESCs, despite the fact that these complexes are clearly involved in gene repression in some other contexts (Akasaka et al, 2001;Moussa et al, 2019;O'Carroll et al, 2001;Pasini et al, 2007). One possibility is that H2AK119ub1 directly disrupts RNA Pol II activity (Stock et al, 2007;Zhou et al, 2008), as suggested by in vitro transcription assays (Aihara et al, 2016;Nakagawa et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, distinct noncatalytic and catalytic activities of cPRC1 and vPRC1 might further promote robustness of repression in the face of developmental transitions. To this extent, we have recently shown that ectopic recruitment of cPRC1 or vPRC1 can initiate transcriptional repression, yet only cPRC1 can engage in a feedback mechanism with PRC2 to promote long-term epigenetic silencing (60). Hence, sequence-specific binding of vPRC1 might facilitate formation of repressive chromatin, which is subsequently propagated through replication and cell division by cPRC1.…”
Section: Discussionmentioning
confidence: 99%